MAHARASA – IT’S CONTROVERSIES WSR TO GRAHYA LAKSHANA - Kumar Anju Revi; Misra Abhaya Kumar; Mohanan Arun; P K Vineeth (International Journal of Applied Ayurved Research, 2017)
Uncertainity in Ayurveda is reflected in the interpretation of names and description of drugs found in the ancient treatises like Charaka Samhita, Susrutha Samhita, etc. Ayurvedic trea-tises were also handwritten before the establishment of British rule, by a handful of dedicated workers who believed that Ayurveda is built by the rationale of observation, ex-periment, induction and deduction. Due to lack of scientific names in the original texts, under one name, different plants are known in different parts of the country as per the de-scription, which makes the drug controversial. These controversies lead to decline in the quality and standards of the ayurvedic compound preparations. Maharasa group of drugs ex-plained in the various Rasashastra textbooks are said to be most nearer to Parada (Mercury). These are used in various lohavedha (Process of conversion of lower to higher metals) and dehavedha (therapeutical action) aspects. But the drugs which are mentioned as Maharasa in the treatises and the drugs available now in market shows higher controversies.